An observational cohort study to determine efficacy, adherence and outcome of the early initiation of pressure support ventilation during mechanical ventilation. Issue 1 (14th May 2014) - Glover, Guy; Connolly, Bronwen; Di Gangi, Stefania; Ayers, Lisa; Terblanche, Marius; Beale, Richard; Hart, Nicholas
Abstract : Background: Timely initiation of weaning from mechanical ventilation (MV) is important. Non-validated screening criteria may delay weaning if too prescriptive. This study observed physician-led utilisation of pressure support ventilation (PSV), referenced to four reported conventional screening criteria hypothesising that these criteria would have delayed the weaning progress. Methods: A prospective observational cohort study of adult patients receiving MV in a 30-bed university hospital intensive care unit (ICU). Logistic regression analysis identified factors associated with PSV failure. Outcome is reported according to adherence to the screening criteria. Results: 209 patients were included (age 62.6±15.9 years, male:female 115:94, Acute Physiology and Chronic Health Evaluation (APACHE) II 16.7±6.1). Median (IQR) time to initiate PSV was 11.0 (5.0–22.0) h, and duration of weaning to extubation was 43.0 (13.0–121.5) h. PSV weaning was initiated despite significant hypoxia (partial pressure of arterial oxygen to fraction of inspired oxygen ratio (PaO2 :FiO2 ) 35.8±15.9 kPa), moderate positive end-expiratory pressure levels (7.5±2.5 cm H2 O), deep sedation (44% Richmond Agitation and Sedation Scale (RASS) ≤−3) and cardiovascular instability (48.8%). At PSV initiation, 85% of patients violated at least one screening criterion, yet 74.6% of patients remained stable for 24 h and 25.4% of patients were successfully extubated within 12 h. There was no association between individual screening criteria and PSV failure. Failure to sustain a PSV trial was associated with ventilation >7 days (RR=2.12 (1.33 to 3.38), p=0.002) and ICU mortality (RR=2.94 (1.46 to 5.94), p=0.002). Conclusions: Physician-led transition to PSV and weaning was often initiated early and successfully before patients fulfilled conventional screening criteria. Failure to sustain a PSV trial could be an early indicator of prolonged MV and ICU mortality and warrants further investigation. These data support the view that current screening criteria may delay initiation of weaning.